The new world order ideology and Africa : understanding and appreciating ambiguity, deceit and recapture of decolonized spaces in 21st century historical argument and presentation - Mentan, Tatah, 1948- (Langaa Research & Pub., 2010)
The New World Order Ideology expressed in the form of neoliberal globalization has been used by numerous politicians, scholars and media men through the ages. It refers to a worldwide conspiracy to effect complete and total control over the planet through money farming. This book examines the case of Africa put directly on the chopping board as client states by this ideology ñ when less hampered by idealistic slogans as human rights, raising living standards and democratization ñ to better the achievement of the agenda of the money farmers whose goal is to establish government by loan operations. The money farmersí strategy, as in credit card companies, is to lend as much as the subject target can borrow and still pay fees, charges and interest payments. This means to encourage them to borrow, loan after loan, consolidate all other loans and keep lending ñ up until the crop of foreign exchange seems in jeopardy. The ideal from the Lending Agency viewpoint is to get an African country maxed out on loans to the point that it actually operates all of its government and the nation on LOANS. Once that goal is achieved, you basically have a never ending crop of FOREIGN EXCHANGE from helpless and hopeless African governments and people. Here is Tatah Mentan at his trenchant best!